ANALISIS PENGARUH FACEBOOK TERHADAP PERILAKU INDIVIDU (STUDI PADA PELAJAR SMK/SMU DI KOTA SURAKARTA) - Irwan Christanto Edy; Heriyanta Budi Utama (STIE AUB Surakarta, 2013)
The title of this research was an analysis the effect of facebook toward the individual behavior (a study to the students of SMK/SMU in Surakarta). The aimed of the research was to prove that the use of facebook influenced to the individual behavior. The objects were SMK/SMU’s students in Surakarta. Data were taken by using a simple random was gotten 132 respondents. This study used analysis tools such as 1) test the validity and reliability of the instrument, 2) descriptive statistical analysis, 3) The analysis of Structural Equition Modeling. Instrument test result showed that all items questions used in the questionnaire were valid and reliable. Descriptive analysis described the characteristics of the respondents by gender, Internet applications, support the school in the provision of Internet invest-ment. The Descriptive analysis stated that the majority of respondents understood of facebook. SEM analysis results that the use (application) of facebook has significant effect on individual behavior, where individual behavior was measured by indicators of attitude, personality, learning and individual perception. T-test results indicated that 1) the application of facebook has significant effect on individual attitudes, 2) application of facebook has significant effect on individual personality, 3) application of facebook has significant effect on individual learning, 4) facebook applications has significant effect on individual perceptions. This study proved that the use of facebook has significant effects on individual behavior. Keywords: facebook, attitude, personality, learning, perception